The Role of AIRE Deficiency in Infertility and Its Potential Pathogenesis - Zou, Xueyang; Zhang, Yi; Wang, Xiaoya; Zhang, Rongchao; Yang, Wei (Frontiers in Immunology, 2021)
The increasing number of patients with infertility is recognized as an emerging problem worldwide. However, little is known about the cause of infertility. At present, it is believed that infertility may be related to genetic or abnormal immune responses. It has long been indicated that autoimmune regulator (AIRE), a transcription factor, participates in immune tolerance by regulating the expression of thousands of promiscuous tissue-specific antigens in medullary thymic epithelial cells (mTECs), which play a pivotal role in preventing autoimmune diseases. AIRE is also expressed in germ cell progenitors. Importantly, the deletion of AIRE leads to severe oophoritis and age-dependent depletion of follicular reserves and causes altered embryonic development in female mice. AIRE-deficient male mice exhibit altered apoptosis during spermatogenesis and have a significantly decreased breeding capacity. These reports suggest that AIRE deficiency may be responsible for infertility. The causes may be related to the production of autoantibodies against sperm, poor development of germ cells, and abnormal ovarian function, which eventually lead to infertility. Here, we focus on the potential associations of AIRE deficiency with infertility as well as the possible pathogenesis, providing insight into the significance of AIRE in the development of infertility.